A hot mini-Neptune in the radius valley orbiting solar analogue HD 110113. Issue 4 (25th January 2021) - Osborn, H P; Armstrong, D J; Adibekyan, V; Collins, K A; Delgado-Mena, E; Howell, S B; Hellier, C; King, G W; Lillo-Box, J; Nielsen, L D; Otegi, J F; Santos, N C; et al.
ABSTRACT: We report the discovery of HD 110113 b ( TESS object of interest-755.01), a transiting mini-Neptune exoplanet on a 2.5-d orbit around the solar-analogue HD 110113 ( T eff = 5730 K). Using TESS photometry and High Accuracy Radial velocity Planet Searcher (HARPS) radial velocities gathered by the NCORES program, we find that HD 110113 b has a radius of 2.05 ± 0.12 R⊕ and a mass of 4.55 ± 0.62 M⊕ . The resulting density of 2.90^+0.75_-0.59 g cm −3 is significantly lower than would be expected from a pure-rock world; therefore HD 110113 b must be a mini-Neptune with a significant volatile atmosphere. The high incident flux places it within the so-called radius valley; however, HD 110113 b was able to hold on to a substantial (0.1–1 per cent) H–He atmosphere over its ∼4 Gyr lifetime. Through a novel simultaneous Gaussian process fit to multiple activity indicators, we were also able to fit for the strong stellar rotation signal with period 20.8 ± 1.2 d from the RVs and confirm an additional non-transiting planet, HD 110113 c, which has a mass of 10.5 ± 1.2 M⊕ and a period of 6.744^+0.008_-0.009 d.